A Creole nation : national integration in Guniea -Bissau - Köhl, Christoph (Berghahn, 2018)
Despite high degrees of cultural and ethnic diversity as well as prevailing political instability, Guinea-Bissau's population has developed a strong sense of national belonging. By examining both contemporary and historical perspectives, A Creole Nation explores how creole identity, culture, and political leaders have influenced postcolonial nation-building processes in Guinea-Bissau, and the ways in which the phenomenon of cultural creolization results in the emergence of new identities.